Practical Implementation of Core Indicators for Sustainable Development Reporting - United Nations Conference on Trade; Development (United Nations, 2021)
This publication contains two volumes and presents case studies on practical implementation of core indicators for sustainable development reporting with a view to facilitate the sharing of good practices among Member States. Since the adoption of the 2030 Agenda for Sustainable Development in 2015, member States of the United Nations have focused on establishing priorities and plans towards its implementation while also monitoring progress. To support this process, a global indicator framework was created, establishing 169 targets and 232 indicators for the 17 Sustainable Development Goals (SDGs). Relevant data on companies’ contribution to SDGs is important to reaching targets and indicators, but achieving such an objective requires further efforts towards the harmonization and comparability of enterprise data to make them useful in assessing progress. Responding to this challenge, UNCTAD has identified the need for baseline SDG indicators for companies, which would allow for the effective measurement of the private sector's contribution to sustainable development. Volumes I and II offer a compendium of case studies.